THE EFFECT OF PRODUCT ATTRIBUTES AND SERVICE QUALITY TOWARDS DECISIONS FOR PURCHASE OF SUZUKI ERTIGA CAR CONSUMERS IN. TRANS SUMATERA AGUNG MEDAN - Rendy Chandra; Hendry Hendry; Deni Faisal Mirza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
Researchers took the object of research at PT. Trans Sumetera Agung Medan. object selection is caused due to a decrease in purchasing decisions Suzuki Ertiga cars. Decline in consumer purchasing decisions can be seen from the decline in sales in recent months. The decrease in sales was influenced by factors of product attributes and service quality. The problem of product attributes is the lack of innovative design on Suzuki Ertiga products, making it difficult to sell. Whereas in service quality, salespeople who are less informative, salesmen who are not friendly, result in consumers choosing other similar products. Theories used in research are marketing management theories relating to product attributes, service quality and purchasing decisions. Methods of data collection by interview, distribution of questionnaires and study of documentation. The analytical method used is multiple linear regression, the coefficient of determination of simultaneous testing (F-Test) and partially (t-Test). The population used is consumers of 168 people and the number of samples used is 118 consumers with sample determination techniques using Slovin formula. Simultaneous test results show that product attributes and service quality have a positive and significant effect on purchasing decisions of Suzuki Ertiga cars at PT. Trans Sumatera Agung Medan with a coefficient of determination of 45% and the remaining 55% is explained by independent variables not examined such as promotion, product quality, and brand ... Based on the results of the study, it can be concluded that product attributes and service quality affect the purchase decision of the car Suzuki Ertiga at PT. Trans Sumatra Agung Medan.